Rational Design of Highly Comprehensive Liquid-Like Coatings with Enhanced Transparency, Concerted Multi-Function, and Excellent Durability A Ternary Cooperative Strategy - Su, Yang (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.